2023
DOI: 10.1021/acs.langmuir.2c03353
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide/Phosphoric Acid Modification of Hydrochars for Sulfamethoxazole and Carbamazepine Adsorption: The Role of Oxygen-Containing Functional Groups

Abstract: Emerging pollutants, such as sulfonamide antibiotics and pharmaceuticals, have been widely detected in water and soils, posing serious environmental and human health concerns. Thus, it is urgent and necessary to develop a technology for removing them. In this work, a hydrothermal carbonization method was used to prepare the hydrochars (HCs) by pine sawdust with different temperatures. To improve the physicochemical properties of HCs, phosphoric acid (H 3 PO 4 ) and hydrogen peroxide (H 2 O 2 ) were used to mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The infrared spectroscopy analysis results of the ROPAC spent homogeneous catalysts are shown in Figure 7 , where Rh-1 and Rh-2 represent the infrared spectra of the ROPAC spent catalyst before and after oxidation treatment, respectively. By comparative analysis, it can be observed that the absorption peak at 3485 cm −1 corresponds to the O-H stretching vibration [ 37 ]. The significant increase and broadening of this absorption peak indicate the presence of -OH entering the oil phase during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The infrared spectroscopy analysis results of the ROPAC spent homogeneous catalysts are shown in Figure 7 , where Rh-1 and Rh-2 represent the infrared spectra of the ROPAC spent catalyst before and after oxidation treatment, respectively. By comparative analysis, it can be observed that the absorption peak at 3485 cm −1 corresponds to the O-H stretching vibration [ 37 ]. The significant increase and broadening of this absorption peak indicate the presence of -OH entering the oil phase during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…244 Furthermore, a large number of CC bonds can be broken and the refractory organic matter in the biomass structure can be removed by the strong oxidation reaction of H 2 O 2 , resulting in an increase in the content of C and aromaticity of hydrochar-based materials. 245…”
Section: Functionalization Of Hydrochar Materialsmentioning
confidence: 99%
“…These contaminants will be transported through the strata, potentially polluting groundwater, surface water, and deep soil layers. , The microstructure of clay particles impacts the reactivity, adsorption capacity, and transport properties of the soil, which in turn affect the migration and diffusion of pollutants in the natural environment . Furthermore, pollutants will cause changes in the chemical properties of the pore water, and for clay soil, which is extremely sensitive to the hydration environment, the impact on the microstructure of clay is undoubtedly tremendous. …”
Section: Introductionmentioning
confidence: 99%